Sistem Pakar Diagnosis Penyakit Tanaman Padi Dengan Metode Teorema Bayes - Nurul Kholifah (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2023)
One of the cultivated plants is rice, oryza sativa in Latin, although some varieties are wild rice. Rice cultivation began in Indonesia around 15000 BC, although it is thought to have originated in India or Indochina. Rice is the most important crop in agrarian countries like China, India, Bangladesh and Indonesia. The japonica and indica groups usually contain rice plants. According to archaeological evidence, japonica rice was first domesticated around 9,000 years ago in the Yangtze Valley in southern China. Meanwhile, around 5,000 years ago, indica rice was first grown in the Ganges River valley. Rice-producing grass plants fall into this category. For most Indonesians, rice is a staple food. At the time of growth, rice plants are susceptible to various diseases which cause farmers to fail to harvest. To find out the diseases that attack rice plants, an expert who can diagnose rice plant diseases is needed. An expert is someone who understands the problem of diagnosing a disease. However, the lack of agricultural officers/extensioners in the Seputih Banyak District area. The purpose of this research is to apply an expert system using the Bayes theorem method to overcome problems regarding rice plant diseases and the limitations of agricultural officers/extensioners. And can be accessed by farmers anywhere when they need an epert system to diagnose a disease that attack rice plants without having to need assistance from extension  agricultural extension officers.